Primary Health Care in a Developing Economy: Issues of Job Autonomy, Resources, Quality of Care at the District Level in Zimbabwe - Makwarimba, Edward (My University, 1996)
Primary Health Care (PHC) is a structural expression of an alternative form of health-care provision whose central philosophy is equity. Since the appearence of this institution on the scene in the late 1970s, numerous developing countries have embraced its tenets in a bid to either replace or counteract the curative approach characteristic of Western biomedicine with varying degrees of success. Concomitant with this is the proliferation of studies, most of which have focused on: the cultural acceptability of PHC technologies; the inequitable distribution of health resources; accessibility of health care facilities. etc. - all of which are germane and laudable attempts to make health a basic human right. However, such research foci neglect some organisational structures upon which the effectiveness of PHC programmes is contingent. Furthermore, the personal experiences of both providers and consumers are often neglected.
The purpose of this exploratory and qualitative study is to investigate the relationship between job autonomy/participation in policy decision making and (a) the quality of health care provision and (b) the effectiveness of the PHC programme, with burnout and job satisfaction/dissatisfaction as the intermediate variables. Empirical research was undertaken in the district of Mutoko (Zimbabwe), with Mutoko District Hospital as the primary site. Data were collected through unstructured interviews, observation and government records.
Analysis of the data reveals that, apart from those with supervisory and managerial responsibilities, most personnel do not show much desire for greater job autonomy/participation in policy decision making. However, the analysis shows that job autonomy/participation in policy decision making and resources have both a direct and an indirect (through the intermediate variables) effect on the quality of health care and the effectiveness of the PHC programme. Furthermore, the analysis indicates that lack of resources, personnel shortages (which lead to work/role overload) and low salaries are the major causes of job burnout and job dissatisfaction in the district health system.
Analysis of consumers' situations and experiences to determine quality of care suggests that the effectiveness of PHC and the utilisation of health services cannot be simply assumed by encouraging people to use them. Therefore, addressing the major concerns noted above is essential to ensure geographical, economic, intellectual and psychological accessibility and that primary health care services become effective in practice.
Keywords: Sociology; Sociology